New approaches and principles in foreign language teaching - Kultanova, Zh.M. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
The article deals with the basic approaches and methods in foreign language teaching. The approaches are rather new and deal with the basic components of the methods, with their positive and negative aspects. It is told about the main approaches like communicative and conscious approaches, oral integrated and multimedia approaches, differentiated and integrated instruction; it is given the goal of language teaching and what motivation in foreign language learning is. The author considers the next principles of foreign language teaching like the principle of conscious approach, principle of activity, principle of differentiated and integrated instruction and others.
Шетел тілін оқытудың жаңа тəсілдері мен əдістері
Новые подходы и принципы в обучении иностранному языку
Keywords: methods and approaches; methodology of foreign language teaching; principle of individualization; the goals of language teaching; motivation; mechanical and cognitive adoption; pupil’s consciousness; to ensure activity; cognitive style; positive motivation in learning; concrete and analytical learning style